Pengaruh Model Discovery Learning Terhadap Kemampuan Berfikir Kritis Matematika Siswa Kelas V Di Sekolah Dasar - Putri, Yulia Cahya; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
Abstract             This research aimed to determine the effect of the Discovery Learning model on mathematical critical thinking skills of fifth grade students of Public Elementary School 02 Aur Kuning, Bukittinggi City on simple statistical material. This research was quantitative research with the experimental method. This Quasi Experiment research used Non-equivalent control group design. The population in this research was Elementary Schools in group II in Aur Birugo Tigo Baleh and the sample technique used was cluster random sampling. The data collection technique used was test in essay form and non-test using an observation sheet. The data were analyzed using t-test to see the effect of two average values after the normality test and homogeneity test. The results showed that the average of post-test in experiment class was 80.4 and 78.27 in control class. Analysis of t-test both in experiment and control classes was obtained tcount = 2.8 and ttable = 1.701 at a significant level of 0.05. Hence tcount> ttable then Ha was accepted. Thus it can be concluded that the Discovery Learning model had a positive effect on the mathematical critical thinking skills of the fifth grade students of Public Elementary School 02 Aur Kuning, Bukittinggi in simple statistical material.